Engagement of gcFKBP5/TRAF2 by spring viremia of carp virus to promote host cell apoptosis for supporting viral replication in grass carp. (February 2022) - Chen, Yu; Zhao, Mengjing; Fan, Xiongwei; Zhu, Ping; Jiang, Zhaobiao; Li, Faxiang; Yuan, Wuzhou; You, Shiqi; Chen, Jimei; Li, Yunxuan; Shi, Yan; Zhu, Xiaolan; et al.
Abstract: Spring viremia of carp virus (SVCV) causes severe morbidity and mortality in grass carp ( Ctenopharyngodon idellus ) in Europe, America and several Asian countries. We found that FKBP5 (FK506-binding protein 5) is an SVCV infection response factor; however, its role in the innate immune mechanism caused by SVCV infection remains unknown. This study cloned gcFKBP5 (grass carp FKBP5) and made its mimic protein structure for function discussion. We found that gcFKBP5 expression in the primary innate immune organs of grass carp, including intestine, liver and spleen, was highly upregulated by SVCV in 24 h, with a similar result in fish cells by poly(I:C) treatment. gcFKBP overexpression aggravates viral damage to cells and increases viral replication. Furthermore, SVCV engages gcFKBP5 interacting with TRAF2 (tumour necrosis factor receptor-associated factor 2) to promote host cell apoptosis for supporting viral replication. The enhanced viral replication seems not to be due to the repression of IFN and other antiviral factors as expected. For the first time, these data show the pivotal role of gcFKBP5 in the innate immune response of grass carp to SVCV infection. Highlights: ●We cloned the gene sequence of grass carp FKBP5(gcFKBP5) for the first time and constructed the related expression vector. ●gcFKBP5 was activated in the immune organs of grass carp. ●Over-expression of gcFKBP5 aggravated the damage of virus infection and increased the replication of virus. ●gcFKBP5 interacted with TRAF2 during viral replication. ●gcFKBP5 did not inhibit IFN or other antiviral factors production during virus infection.